Immunocorrective Therapy of Chronic Recurrent Aphthous Stomatitis - Maxmudov Shaxboz Muzaffarovich; Xolboyeva Nasiba Asrorovna; Tolliboyev Otabek G’ayrat ug’li (Genius Journals, 2023)
Lycopide in the complex treatment of patients with chronic recurrent aphthous stomatitis contributes to the normalization of local protection of the oral cavity, accelerates the healing time and reduces the number of relapses
Keywords: chronic recurrent aphthous stomatitis; local immunity; immunocorrection